Colonization of host plants by the fire blight pathogen Erwinia amylovora marked with genes for nioluminescence and fluorescence - Bogs, Jochen; Bruchmüller, Iris; Erbar, Claudia; Geider, Klaus (Phytopathology, 1998)
To follow the movement of Erwinia amylovora in plant tissue without dissection, this bacterium was marked with either the lux operon from Vibrio fischeri or the gfp gene from the jellyfish Aequorea victoria, both carried on multicopy plasmids and expressed under the control of the lac promoter from Escherichia coli. Movement of the pathogen was visualized in leaves, stems, and roots of apple seedlings, and migration of E. amylovora was traced from inoculation sites in the stem to as far as the roots. Green fluorescent E. amylovora cells were observed in the xylem and later appeared to break out of the vessels into the intercellular spaces of the adjacent parenchyma. Inoculation in the intercostal region of leaves caused a zone of slow necrosis that finally resulted in bacterial invasion of the xylem vessels. Labeled bacteria could also be seen in association with the anchor sites of leaf hairs. Distortion of the epidermis adjacent to leaf hairs created openings that were observed by scanning electron microscopy. As the intercostal region, the bases of leaf hairs provided E. amylovora access to intact xylem vessels, which allowed further distribution of the pathogen in the host plant.